Testes and body weight alteration related cardamom extract administration in mice - Tyagita Hartady; Arvia Nisrina Praditha; Nabila Ayu Faza; Rini Widyastuti (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2019)
Cardamom is known as a plant with millions of benefits and it is known to contain aphrodisiac substances. The role of cardamom as an aphrodisiac need to be studied more deeply from the scientific point of view. The experimental object is a 3-month-old male white mice (Mus musculus albinus) with an average weight of about 30-35 grams. After being acclimatized for approximately 2 weeks, 35 mice were divided into 3 groups based on the dose of cardamom extract. At the end of the experiment, the mice will be sacrificed and then the testes were weighed and cauda epididymis were isolated to collect the sperm. Our findings suggested that the dose of administration has important role in affecting the weight of testes and bodies of mice. However, further studies on sperm profiles and optimal administration doses of cardamom extract are highly recommended.